Requirements for cremation architecture in contemporary secularized society - Klára Frolíková Palánová; Jan Kovář; Tomáš Babor; Ivona Dlábiková; Ondřej Juračka (In_Bo, 2015)
Burials of the deceased were always part of life of each society and that remain forever. In Middle European culture based mostly on Christian tradition, it was common place, till the end of 19th Century, for burials in a grave. On the beginning of 20s Century gradually began to apply also cremation. Its supporters pointed on its hygienic superiority compared to classical disposal with deceased. This led to established and gradual development of a new building type – the crematorium. Supporters also promote high quality farewell ceremonies and this resulted in quality burial and cemetery culture during whole 20s Century. The aim is to approach this new building type to the professional public and specify organization and typology for promote high ethic, ceremony, aesthetic and respect.